Studi literatur: Dampak Positif dan Negatif Pengasuhan Otoriter Orang Tua Terhadap Anak - purba, andareas; Zalfa Jihan Aqillah; Afdwikki, M. Izha; Defi Syazana Nadhira; Metha Ariana Milanda (In Trend : International Journal of Trends in Global Psychological Science and Education, 2024)
Family behavior, especially parents, in applying parenting patterns to children greatly affects the growth and development of children, especially in the formation of their personality. Authoritarian parenting explains that parents tend to force children to do things according to their wishes. In this parenting pattern, parents set rules at home that must be obeyed by children. This study aims to investigate the positive and negative impacts of parental authoritarian parenting on children through a literature review. Authoritarian parenting is one of the parenting styles that tends to impose high control and is less supportive of children's independence. This literature review examines several studies that highlight the positive and negative impacts of authoritarian parenting. The results of this literature review provide a deeper understanding of how the positive and negative impacts of parental authoritarian parenting can affect children ranging from children's socioemotional, children's openness, children's morals and behavior, with implications for intervention development and further research in this area.